Efeito do diâmetro do trote em equinos e comparação do efeito clínico de firocoxibe e fenilbutazona na claudicação em equinos - Santos, Rafael Cardoso dos (2024)
Lameness is a clinical sign present in musculoskeletal changes in horses, and its determination, location and treatment are a constant challenge in the veterinarian's clinical routine. This research work aims to evaluate, at trot, the impact of different diameters of the circle on animals without lameness in a straight line, considering the influence on the diameter (6, 10 and 14 meters) on different surfaces (hard and soft). And, secondly, compare the analgesic effect of two non-steroidal anti-inflammatory drugs, a selective inhibitor of cyclooxygenase 2 (COX-2), and a non-selective one (NSAID). In the first study, 19 animals were used and a greater influence on lameness was observed in a diameter of 6 meters on a hard floor surface. In the second study, a greater analgesic effect was observed with the drug firocoxib after 12 hours of administration, however, when compared in the same Time interval analgesia was similar between phenylbutazone and firocoxib. Therefore, we conclude that the diameter of 6 meters on the hard floor surface has a greater influence on lameness and firocoxib, when compared to phenylbutazone, has similar analgesia and can be an alternative in the rotation of anti-inflammatory drugs.